Prohibition of Slavery and Forced Labour - Strban, Grega; Kogej, Katarina (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
The chapter emphasises the continued relevance of Art. 4 of the European Convention on Human Rights (ECHR), which prohibits slavery, servitude and forced or compulsory labour. Despite formal abolition, modern forms of these practices, such as domestic servitude, debt bondage and human trafficking, persist in Europe. Art. 4 is structured around two central prohibitions: the absolute right not to be subjected to slavery or servitude and the prohibition of forced labour, with delimitations regarding work during detention or conditional release, military service, service required during an emergency or calamity and civic obligations. Furthermore, the ECHR imposes positive obligations on states, requiring them to implement effective legislative and administrative frameworks, take operational measures to protect victims and conduct effective and independent investigations.The historical overview traces slavery and forced labour from ancient times to their formal abolition and highlights the first international efforts, such as the 1926 Slavery Convention and ILO Convention No. 29 on Forced Labour. A comparison with other universal and regional human rights instruments underlines their scope of protection and enforcement mechanisms, emphasising the ECHR’s advantage in providing individuals direct access to the European Court of Human Rights (ECtHR), which issues legally binding decisions. The case law analysis examines key cases, such as Siliadin v. France, where the Court first condemned domestic servitude, and Rantsev v. Cyprus and Russia, which broadened Art. 4 to include human trafficking. It explores cases from Central and Eastern Europe, such as S. M. v. Croatia, M. and Others v. Italy and Bulgaria and Krachunova v. Bulgaria, shaping the Court’s jurisprudence in these regions. Art. 4 provides a strong framework to combat slavery and forced labour, with the ECtHR acknowledging the evolving nature of such violations in modern society and interpreting the Convention as a living instrument. Keywords: ECHR, slavery, forced labour, human trafficking, case law